Simulation of the BFS Algorithm for Determining the Shortest Route to Sawarna Beach, Banten Province - Sigit Auliana; Basuki Rakhim Setya Permana; Iis Nurasiah; Mochammad Darip (Postgraduate, University of Mataram, 2025)
Sawarna Beach, located in Lebak Regency, Banten Province, is a popular tourist destination. However, limited information and poor accessibility remain challenges for potential visitors. Many rely solely on general mapping services, which may not reflect the most efficient routes. This study aims to simulate the Breadth First Search (BFS) algorithm to determine the shortest travel route to Sawarna Beach. The BFS algorithm, effective for unweighted graphs, explores all vertices level by level. A simulation-based quantitative method was employed, and the system was implemented using PHP. The results reveal multiple alternative routes that could serve as references for travelers unfamiliar with the area. While shortest routes were identified, travelers are advised to consider additional factors such as traffic, road conditions, and available facilities.